INTEGRASI KECERDASAN BUATAN DALAM PENINGKATAN PRODUKTIVITAS DAN DAYA SAING EKONOMI SYARIAH MODERN - Muhlis, Muhlis (LPPM STAI Muhammadiyah Probolinggo, 2026)
The development of digital technology, particularly Artificial Intelligence (AI), offers significant opportunities for advancing modern Islamic economics. This study aims to analyze the implementation of AI in the Islamic finance sector, halal MSMEs, and the halal industry, as well as to identify the opportunities, benefits, and challenges associated with its application. The research employs a descriptive qualitative method using a literature review and comparative analysis approach, including secondary case studies from best practices in Indonesia and other countries. The findings indicate that AI plays a role in enhancing operational efficiency, expanding financial inclusion, supporting product innovation, and ensuring compliance with Sharia principles through automation and intelligent data analysis. Nevertheless, the adoption of AI faces several challenges related to regulation, Sharia compliance, ethical data use, privacy, and the limited availability of human resources who understand both AI and Islamic economics. In conclusion, integrating AI into modern Islamic economics is an essential strategy for improving productivity, innovation, and competitiveness within the halal sector in the digital era.